Triglyceride-glucose index and stroke recurrence in elderly patients with ischemic stroke - Wang, Fang; Wang, Jinjing; Han, Yunfei; Shi, Xuan; Xu, Xiaohui; Hou, Chao; Gao, Jie; Zhu, Shuanggen; Liu, Xinfeng (Frontiers in Endocrinology, 2022)
Background and purpose This study aimed to explore the association between triglyceride–glucose (TyG) index and stroke recurrence in elderly patients with ischemic stroke in China. Methods We enrolled ischemic stroke patients aged ≥ 65 years from the Nanjing Stroke Registry Program. The primary endpoint was defined as recurrent stroke within one year after the index stroke. We used multivariable Cox proportional hazards regression models to investigate the association between TyG index and stroke recurrence. We assessed the discriminative ability of TyG index with the receiver operative characteristic and the area under the curve. Results A total of 955 patients (median age, 70.0 [67.0, 75.0]; male sex, 67.2%) from the Nanjing Stroke Registry Program were enrolled. During one year follow-up, 97 (10.2%) elderly patients experienced stroke recurrence. In multivariable analyses, the association between TyG index and stroke recurrence remained significant after adjusting for confounders (quartile 4 versus quartile 1; hazard ratio, 2.073, 95% confidence interval, 1.158-3.711; P = 0.014). The restricted cubic spline showed an increasing trend for TyG index and stroke recurrence (P for non-linearity = 0.072). The area under the curve to predict stroke recurrence with TyG index was 0.719 (95% confidence interval, 0.666-0.772). Besides, TyG index slightly improved the prediction for stroke recurrence. Conclusion Elevated TyG index was associated with stroke recurrence in elderly patients with ischemic stroke. Further studies are warranted to assess the role of TyG index in the development of stroke recurrence in the elderly.